2013
DOI: 10.1089/scd.2012.0615
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Mesenchymal Stem Cell Therapy for Bisphosphonate-Related Jaw Osteonecrosis in Swine

Abstract: Bisphosphonates (BPs), which are used to treat a variety of clinical disorders, have the side effect of jawbone necrosis. Currently, there is no reliable treatment for BP-related osteonecrosis of the jaw (BRONJ) due to a lack of understanding of its pathogenesis. To investigate the pathogenesis of BRONJ and observe the treatment effect of bone marrow mesenchymal stem cell (BMMSC) transplantation, we established a preclinical animal model of BRONJ in miniature pigs (minipigs). After treatment with zoledronic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 27 publications
0
57
1
2
Order By: Relevance
“…Considering important to find preventive strategies in order to ensure and improve survival characteristics in the irradiated tissues and that these studies are impracticable to perform in vivo, because the ethical point of view, it must develop an in vitro protocol [14,15,[23][24][25][26][27].…”
Section: Cutting and Obtaining Blocks Of Dental Enamel And Root Dentinmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering important to find preventive strategies in order to ensure and improve survival characteristics in the irradiated tissues and that these studies are impracticable to perform in vivo, because the ethical point of view, it must develop an in vitro protocol [14,15,[23][24][25][26][27].…”
Section: Cutting and Obtaining Blocks Of Dental Enamel And Root Dentinmentioning
confidence: 99%
“…The determination of effects caused by ionizing radiation, using dose for patients with head and neck cancer, in terms of variations in biochemical composition and surface microhardness [22][23][24][25][26][27][28][29][30][31], as a first step as pathophysiology comprehension, will be helpful for reduced or to eliminate inherent radiotherapy complications. Moreover, it could focus on more details from specific issues as dose reduced fractionation protocols and modalities, as long as data obtained from in vitro studies [31][32][33][34][35][36][37][38][39][40].…”
Section: Cutting and Obtaining Blocks Of Dental Enamel And Root Dentinmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have recently emerged as candidates for BRONJ treatment (Kikuiri et al, 2010;Cella et al, 2011;Gonzalvez-Garcia et al, 2013;Li et al, 2013) due to their capacity to differentiate to other mesenchymal tissues such as bone, cartilage, and adipocytes (Pittenger et al, 1999), and due to the secretion of numerous cytokines with immunomodulatory and proangiogenic activity. Although the mechanisms of the immunosuppressive effects of MSCs have not been clearly defined, it seems that MSCs modulate the function of different cells involved in immune response (Yoo et al, 2009;Kikuiri et al, 2010;Li et al, 2013) (Zuk et al, 2001), and have shown great potential in enhancing wound healing (Toyserkani et al, 2014). Bone-inducing substances such as bone morphogenetic protein 2 (BMP-2) have been used to culture MSCs for treatment of skeletal defects and bone diseases by promoting their differentiation to bone tissue (Cowan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This activity is thought to be largely based on inhibition of T-cell and B-cell proliferation and dendritic cell maturation (Nauta and Fibbe, 2007) and the secretion of a large number of cytokines and growth factors (Chen et al, 2008). MSCs also are able to restore the immunologic imbalance produced by zoledronic treatment (between T helper cells and regulatory T-cells), which may alter the inflammatory response of alveolar socket healing in ZAtreated animals (Kikuiri et al, 2010;Li et al, 2013). However, in our study, inflammatory infiltrates were detected in animals of all groups, with no close relation with osteonecrosis foci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation